Multivariate Analysis of Genetic Diversity Among Sugarcane Clones (Saccharum spp.) - Melaku Tesfa; Esayas Tena; Mulugeta Kebede (Scientifica)
Comprehensive information about genetic diversity in germplasm collection is crucial to efficiently using genetic resources in crop improvement programs. This study used multivariate analysis to assess the genetic diversity of 144 sugarcane genotypes in quantitative traits. The experiment was conducted using a partially balanced lattice design with two replications. Sixteen quantitative traits were measured, including sprouting percentage, tiller count, stalk count, stalk height, stalk diameter, number of internodes, single cane weight, cane yield, sugar yield, Brix%, Pol%, Purity%, Sucrose%, leaf area, leaf width, and leaf length. The data were subjected to univariate and multivariate analyses using SAS and R software, respectively. The analysis of variance depicted significant differences between genotypes in all traits considered. The first four main components contributed 81.44% of the overall variation. PC1 reflected the yield potential of each genotype, whereas PC2 revealed the quality potential of each genotype. The cluster analysis divided the total of 144 genotypes into five distinct clusters regardless of their geographic origin, suggesting the exchange of germplasm between countries that grow sugarcane. Cluster I expressed the highest mean value for stalk height and sugar yield traits; cluster II for sprouting, tiller count, stalk count, single cane weight, number of internodes, and cane yield; cluster III for Pol%, Sucrose%, and Brix%; cluster IV for purity; and cluster V for stalk diameter, leaf width, and leaf area. These findings indicated the existence of significant phenotypic variation between the tested genotypes, and the selection of diverse parents from these clusters could enhance breeding programs by using the maximum heterotic potential and broadening the genetic base through variability in segregant progeny. In conclusion, multivariate analyses successfully revealed the genetic variation among the sugarcane genotypes studied.